Patients eligible for modulator drugs: Data from cystic fibrosis registry of Turkey. Issue 9 (26th May 2020) - Çobanoğlu, Nazan; Özçelik, Uğur; Çakır, Erkan; Şişmanlar Eyüboğlu, Tuğba; Pekcan, Sevgi; Cinel, Güzin; Yalçın, Ebru; Kiper, Nural; Emiralioğlu, Nagehan; Şen, Velat; Şen, Hadice Selimoğlu; Ercan, Ömür; et al.
Abstract: Background: A better understanding of cystic fibrosis transmembrane conductance regulator biology has led to the development of modulator drugs such as ivacaftor, lumacaftor‐ivacaftor, tezacaftor‐ivacaftor, and elexacaftor‐tezacaftor‐ivacaftor. This cross‐sectional study evaluated cystic fibrosis (CF) patients eligible for modulator drugs. Methods: Data for age and genetic mutations from the Cystic Fibrosis Registry of Turkey collected in 2018 were used to find out the number of patients who are eligible for modulator therapy. Results: Of registered 1488 CF patients, genetic analysis was done for 1351. The numbers and percentages of patients and names of the drugs, that the patients are eligible for, are as follows: 122 (9.03%) for ivacaftor, 156 (11.54%) for lumacaftor‐ivacaftor, 163 (11.23%) for tezacaftor‐ivacaftor, and 57 (4.21%) for elexacaftor‐tezacaftor‐ivacaftor. Among 1351 genotyped patients total of 313 (23.16%) patients are eligible for currently licensed modulator therapies (55 patients were shared by ivacaftor and tezacaftor‐ivacaftor, 108 patients were shared by lumacaftor‐ivacaftor and tezacaftor‐ivacaftor, and 22 patients were shared by tezacaftor‐ivacaftor and elexacaftor‐tezacaftor‐ivacaftor groups). Conclusions: The present study shows that approximately one‐fourth of the registered CF patients in Turkey are eligible for modulator drugs. As, frequent mutations that CF patients have in Turkey are different from North American and European CF patients, developing modulator drugs effective for those mutations is necessary. Furthermore, as modulator drugs are very expensive currently, financial support of the government in developing countries like Turkey is noteworthy.